UJI PEMBERIAN PUPUK NPK MUTIARA DAN PUPUK ORGANIK CAIR NASA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo L.) - Jusri Ayu; Edy Sabli; Sulhaswardi Sulhaswardi (UIR Press, 2017)
The study aimed to determine the effect of NPK Mutiara fertilizer and liquid Nasa organic fertilizer as well as each of the main factors on the growth and yield of melon plants (Cucumis melo L). The experimental design used was factorial 4 x 4 in Completely Randomized Design (CRD). The first factor was the administration of NPK Mutiara fertilizer consisting of 4 levels, namely: 0, 5, 10, and 15 grams/plant, and the second factor Nasa liquid organic fertilizer consisted of 4 levels, namely: 0, 3, 6, and 9 cc/plant. so that 16 combinations of treatments were obtained. Each combination of treatments consisted of 3 replications so that 48 units of the plot were obtained. Data from the observations were analyzed statistically (variance analysis) and BNJ advanced tests at the level of 5%. The parameters observed were flowering age, harvest age, stem diameter, fruit weight per fruit, the thickness of fruit flesh, and taste test. Research shows that the interaction of NPK Mutiara fertilizer and Nasa liquid organic fertilizer does not significantly affect all parameters, but singly NPK Mutiara fertilizer and liquid Nasa organic fertilizer give an influence on the parameters of observation. The main influence of NPK Mutiara fertilizer influences all observation parameters, namely flowering age, harvest age, stem diameter, widest leaf area, fruit circumference, fruit weight per fruit, production per plot, and thickness of fruit flesh. The best treatment is the administration of Pearl 5K NPK/plant (K1). While the main factors for the provision of liquid organic fertilizer Nasa affect the parameters of flowering age, harvest age, and widest leaf area. The best treatment is the administration of 6 ml/l water (N2) liquid organic fertilizer.